A novel GRN mutation in an Italian patient with non-fluent variant of primary progressive aphasia at onset: a longitudinal case report - Castelnovo, Veronica; Canu, Elisa; Domi, Teuta; Pozzi, Laura; Vignaroli, Francesca; Spinelli, Edoardo Gioele; Ghirelli, Alma; Tondo, Giacomo; Comi, Cristoforo; Riva, Nilo; Quattrini, Angelo; Carrera, Paola; et al. (Frontiers in Neuroscience, 2023)
Objectives. We report the clinical presentation and evolution of a case with a novel Progranulin gene (GRN) mutation and non-fluent language disturbances at onset. Materials and methods. A 60 years-old, white patient was followed due to a history of language disturbances. Eighteen months after onset, the patient underwent FDG positron emission tomography (PET), and at month 24 was hospitalized to perform neuropsychological evaluation, brain 3T MRI, lumbar puncture for cerebrospinal fluid (CSF) analysis, and genotyping. At month 31, the patient repeated the neuropsychological evaluation and brain MRI. Results. At onset the patient complained prominent language production difficulties, such as effortful speech and anomia. At month 18, FDG-PET showed left fronto-temporal and striatal hypometabolism. At month 24, the neuropsychological evaluation reported prevalent speech and comprehension deficits. Brain MRI reported left fronto-opercular and striatal atrophy, and left frontal periventricular white matter hyperintensities (WMHs). Increased CSF total tau level was observed. Genotyping revealed a new GRN c.1018delC mutation (p.H340TfsX21) mutation. The patient received a diagnosis of nonfluent variant of primary progressive aphasia (nfvPPA). At month 31, language deficits worsened, together with attention and executive functions. The patient presented also with behavioural disturbances, and a progressive atrophy in the left frontal-opercular and temporo-mesial region. Discussion and conclusion. The new GRN p.H340TfsX21 mutation resulted in a case of nfvPPA characterized by fronto-temporal and striatal alterations, typical frontal asymmetric WMHs, and a fast progression towards a widespread cognitive and behavioral impairment, which reflects a frontotemporal lobar degeneration. Our findings extend the current knowledge of the phenotypic heterogeneity among GRN mutation carriers.